Potential of Nanofluids as Cutting Fluids – An Evolution - Virdi, Roshan Lal; Chatha, Sukhpal Singh; Singh , Hazoor (Asian Review of Mechanical Engineering, 2016)
Heat generation is the common phenomenon associated with machining zone. To protect the workpiece from thermal damage , coolant is required at the cutting zone. Cutting fluids commonly known as coolants limit the energy transferred to the work piece . In the past century various cutting fluids have been developed. Still there is a need to control the temperature of cutting zone. Nanofluids are the latest innovations to enhance the heat carrying capacity of lubricants. This paper reviews the latest developments in nanofluids. The review also highlighted the various challenges for the researchers.